If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3z + 2 Reorder the terms: 7 = 2 + 3z Solving 7 = 2 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 7 + -3z = 2 + 3z + -3z Combine like terms: 3z + -3z = 0 7 + -3z = 2 + 0 7 + -3z = 2 Add '-7' to each side of the equation. 7 + -7 + -3z = 2 + -7 Combine like terms: 7 + -7 = 0 0 + -3z = 2 + -7 -3z = 2 + -7 Combine like terms: 2 + -7 = -5 -3z = -5 Divide each side by '-3'. z = 1.666666667 Simplifying z = 1.666666667
| 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 | | x-14.6=20 | | 5(k+2)=3(-4) | | -8m+15+9m-2= | | Y=-10(5)-3 | | n+221=333 | | 5m-13=33 | | 9x^4=3x^2-25 | | 5(5x)+12= | | 5(5x+12)= | | 4n+24=2n+42 | | 3p+5=2p+14 | | 2(13.5)+-1.5y+3y=27 | | 2*2*n*n=54 | | 12x=3x+12 | | 23xn=22135 | | 2(13.5+-1.5y)+3y=27 | | 5(y-3)+2(y+4)=42 | | 18x+6=3x+18 | | 13(12x+15)=7 | | -7y+5(y-4)=-10 | | 536cm=53.6dm |